The Complete Poetical Works of Oliver Goldsmith - Goldsmith, Oliver, 1730?-1774 (Salt Lake City, UT : Project Gutenberg, 2002)
"The Complete Poetical Works of Oliver Goldsmith" by Oliver Goldsmith is a comprehensive collection of the poet's writings, likely compiled in the early 20th century. The volume includes a wide array of his poetry, accompanied by editorial commentary and notes, showcasing the breadth of Goldsmith's talents and his contributions to literature during the 18th century. The opening of this compilation presents Goldsmith's reflections on his life and work, including insights into his personal struggles, aspirations, and the nature of poetry itself. He begins with a dedication to his brother, explaining the wisdom of finding happiness in simplicity over fame and fortune, before exploring themes such as the fleeting nature of happiness across different societies. The preface sets the stage for the primary poems, indicating that his works will delve into the joys and sorrows of the human experience, as well as address the conflicts between personal desires and societal expectations. (This is an automatically generated summary.)
Release date is 2002-11-01
Amy E Zelmer, Barb Grow, Derek Thompson and David Widger
Keywords: English poetry; Literature -- Collections